If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + 2(y + 3) = 12 Reorder the terms: Y + 2(3 + y) = 12 Y + (3 * 2 + y * 2) = 12 Y + (6 + 2y) = 12 Reorder the terms: 6 + Y + 2y = 12 Solving 6 + Y + 2y = 12 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + Y + -6 + 2y = 12 + -6 Reorder the terms: 6 + -6 + Y + 2y = 12 + -6 Combine like terms: 6 + -6 = 0 0 + Y + 2y = 12 + -6 Y + 2y = 12 + -6 Combine like terms: 12 + -6 = 6 Y + 2y = 6 Add '-2y' to each side of the equation. Y + 2y + -2y = 6 + -2y Combine like terms: 2y + -2y = 0 Y + 0 = 6 + -2y Y = 6 + -2y Simplifying Y = 6 + -2y
| -7y+12=-2 | | x(4)+7-3=8 | | 20x-5=35 | | V=12zqj | | 5.5/4=x | | 3x-12xy-9x(9x)= | | x/8-2=10 | | 4c+d+3c+2d= | | S=2b(a+c) | | =((-5x-1)+(2x^2))x | | 5x+2x-4x-5=16 | | 12a^2-41a+24= | | Y=4(-3x+5)-9 | | y=5x+23 | | 36timesn=12 | | 4t+14=6t+8 | | -30=-8y-12+2y | | 5y+4=7y-2 | | 265+48x=265 | | 3s-4(20-s)=18 | | 8x-6+6x+8=180 | | 4x+9x*2=65 | | 8x^5-4x=4 | | (2p-9)(2p-9)=0 | | 3b+4b=-8b | | 8x^5-4x=4x | | 8t+5p=220 | | 5x+14-x=-10 | | 4(c+10)=3(x+15) | | -6*2*2+5*2*3*3+2*3*1*1= | | 2a^2+9a+7= | | -(x+1)=-4x-2 |